Phospholipid association reduces the gastric mucosal toxicity of aspirin in human subjects - Anand, Bhupinderjit S; Romero B.S, Jim J; Sanduja, Sudershan K; Lichtenberger, Lenard M (The American journal of gastroenterology, 1999)
OBJECTIVE: In previous studies on rats, we have shown that aspirin (ASA)-induced injury to the gastric mucosa is markedly reduced or completely abolished if ASA is chemically associated with the phospholipid, phosphatidylcholine (PC). We have also shown that the protective effect of PC does not influence the ability of ASA to inhibit mucosal cyclooxygenase (COX) activity in the stomach and other tissues. We therefore sought to assess the effect of PC-associated ASA (ASA/PC) on the gastric mucosa of normal volunteers and to compare the results with the use of ASA alone. METHODS: Sixteen normal healthy subjects were administered ASA or ASA/PC in a randomized, double-blind, crossover study. The subjects received ASA in a dose of 650 mg three times a day for 3 days or an equivalent dose of ASA chemically associated with PC. Endoscopy was performed at baseline and again on the morning of day 4, after the subjects had taken the final dose of the test drug. On both occasions, antral biopsy specimens were obtained for the assessment of mucosal COX activity and prostaglandin concentration. RESULTS: The number (mean ± SD) of gastric erosions seen with the ASA/PC formulation was significantly less than when ASA was used alone (8.7 ± 10.7 vs 2.9 ± 4.3; p < 0.025). A similar trend was seen in the duodenum but the difference was statistically not significant. The antral mucosal COX activity, as well as the level of prostaglandin 6-keto PGF 1α, were reduced significantly (80–88%) and to a similar extent by both ASA and ASA/PC. CONCLUSIONS: The present study shows that acute aspirin-induced damage to the gastric mucosa can be reduced by chemically associating ASA with PC. The mechanism of mucosal protection provided by this compound is not related to any alteration in the ability of ASA to inhibit mucosal COX activity. We believe this protection is attributable to the maintenance of the defensive hydrophobic barrier of the gastric mucosa.